The Role of Optimism on Self-Efficacy in Memorizing the Qur'an of Elementary School Students - Aurana Zahro El Hasbi; Yulia Hairina; Mulyani Mulyani (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2022)
Students who have an optimistic attitude are expected to have a strong belief in their abilities. With optimism, students who memorize the Qur'an can show various good behaviors to maximize their potential, thereby strengthening self-efficacy so that they can continue to memorize the Qur'an and complete it based on the target. This study aims to determine the role of optimism and self-efficacy in memorizing the Qur'an. This study used quantitative research using a questionnaire to collect the data. The participants were 100 students of Elementary School (SD) X who participated in the tahfiz program. The optimism scale is based on aspects of Seligman's theory, namely permanence, pervasiveness, and personalization. In contrast, the self-efficacy scale is based on aspects of Bandura's theory, namely level, generality, and strength. Data analysis used a simple linear regression test. The results showed a significant role between optimism and self-efficacy, which was 44.9% (R=0.449, p=0.00<0.05). The regression equation between the optimism and the self-efficacy variables was positive, with Y= 13.379+0.508X. This equation means that for every 1% addition of student optimism, the student's self-efficacy will increase by 50.8%. Based on these calculations, it can be concluded that the higher the optimism, the higher the self-efficacy in memorizing the Qur'an in SD X Banjarmasin students.